University Social Responsibility and its implementation: a scoping review - Olvera León, Guadalupe del Carmen; Sánchez-Armáss Cappello, Omar; Palacios Rodríguez, Oscar Alejandro; Medina Orta, Sayra Yesenia; Armendáriz Zarazua, Roxana Elizabeth (Emerging Trends in Education, 2022)
The purpose of this study was to explore the recent empirical research on University Social Responsibility (USR). A literature review was performed following Arksey & O’Malley’s scoping review design. Results show that most studies have been published in Latin America, in Spanish and address the concepts, teaching and problems related with USR. The literature review shows the USR concept has incorporated a myriad of dimension, particularly integrating environmental care. Even though most studies were qualitative, diverse methodological approaches were employed, so that there is no consensus on what is defined as the most relevant. The USR evaluation within universities should be based on empirical data that allows for decision making in terms of teaching, research and outreach, considering that the current social issues demand solutions based on URS principles and a joint effort from universities, communities and other sector. Keywords: Social responsibility; Universities; Literature; revision